Выявление линейно-независимых факторов управления стадией подготовки сырья в процессе изомеризации легких бензиновых фракций - Кондратов, Сергей Алексеевич; Сидоренко, А. В. (Eastern-European Journal of Enterprise Technologies, 2009)
It is offered the procedure of an establishment of linearly-independent operating factors by the analysis of own values of a correlation matrix of data and sizes of determinants of submatrixes of a correlation matrix. The approach is illustrated on an example of the data of starting operations of a stage of preparation of raw material of technological process of light naphtha fractions isomerization